Natural history and biology of the Tiannan Crocodile Newt, Tylototriton yangi (Urodela: Salamandridae) at Gejiu, Yunnan province, China with its conservation implications - Axel Hernandez; Mian Hou (Nature Conservation Research: Заповедная наука, 2018)
The natural history of newly discovered species among the genus Tylototriton in South-Eastern Asia is poorly known to date, and most of the species are threatened by extinction. The description of their ecology is crucial to determine their survival status and successful reproduction for conservation purposes. In this study, we assessed the microhabitat preferences of Tylototriton yangi at the type locality, Gejiu, Yunnan province, China, with the Visual Encounter Survey method and by using new important materials. The main habitat is located within a humid subtropical climate and is composed of a large karstic mountain containing some patch of secondary mixed forests and plantations such as tomato fields, pepper and cabbage that are surrounded by scrubs, grasses and small ponds. We provided a complete diagnosis with new morphological data analysing ten adult individuals from the type series to establish a formal description which is absent from the first original description. We compared our results with other related taxa of the genus Tylototriton to updated key determinants between similar species. Thus, we analysed the population structure and the behaviour of T. yangi during a period of ten years, 2008–2017, to assess its survival status and to determine the main threat factors. A total of 186 specimens were found during the whole study predicting a small population inhabiting the type locality, Gejiu. Consequently, T. yangi is now regarded as a highly threatened species that need more attention of Chinese authorities and we suggest regarding it as Endangered due to its small distribution range, the low number of adult specimens observed and ongoing exploitation.